Health Outcomes Associated With Having an Oophorectomy Versus Retaining One's Ovaries for Transmasculine and Gender Diverse Individuals Treated With Testosterone Therapy: A Systematic Review. (10th July 2022) - Kumar, Sahil; Mukherjee, Smita; O'Dwyer, Cormac; Wassersug, Richard; Bertin, Elise; Mehra, Neeraj; Dahl, Marshall; Genoway, Krista; Kavanagh, Alexander G.
Abstract: Introduction: The transmasculine and gender diverse (TMGD) spectrum includes transgender men and non-binary individuals whose sex was assigned female at birth. Many TMGD patients pursue treatment with exogenous testosterone to acquire masculine characteristics. Some may choose to undergo gynecological gender-affirming surgery for total hysterectomy with bilateral salpingectomy and/or bilateral oophorectomy (TH/BSO). The decision to retain or remove the ovaries in the setting of chronic testosterone therapy has implications on reproductive health, oncologic risk, endocrine management, cardiovascular health, bone density and neurocognitive status. However, there is limited evidence on the long-term outcomes from this intervention. Objective: Here we review health-related outcomes of oophorectomy in TMGD population treated with chronic testosterone therapy in order to guide clinicians and patients in the decision to retain or remove their ovaries. Method: We conducted a systematic literature review following PRISMA guidelines. MEDLINE, EMBASE, ClinicalTrials.gov, and Cochrane Library databases were searched for peer-reviewed studies published prior to October 26, 2021 that: (i) included transgender men/TMGD individuals in the study populations; (ii) were full-text randomized controlled studies, case reports, case series, retrospective cohort studies, prospective cohort studies, qualitative studies, and cross-sectional studies; and (iii) specifically discussed ovaries, hysterectomy, oophorectomy, ovariectomy, or gonadectomy. Results: We identified 469 studies, of which 39 met our inclusion criteria for this review. Three studies discussed fertility outcomes, 11 assessed histopathological changes to the ovaries, 6 discussed ovarian oncological outcomes, 8 addressed endocrine considerations, 3 discussed cardiovascular health outcomes, and 8 discussed bone density. No studies were found that examined surgical outcomes or neurocognitive changes. Conclusion: There is little information to guide TMGD individuals who are considering TH/BSO versus TH/BS with ovarian retention. Our review suggests that there is limited evidence to suggest that fertility preservation is successful after TH/BS with ovarian retention. Current evidence does not support regular reduction in testosterone dosing following oophorectomy. Estradiol levels are likely higher in individuals that choose ovarian retention, but this has not been clearly demonstrated. Although bone mineral density decreases following oophorectomy, data demonstrating an increased fracture risk are lacking. No studies have described the specific impact on neurocognitive function, or changes in operative complications. Further research evaluating long-term health outcomes of oophorectomy for TMGD individuals treated with chronic testosterone therapy is warranted to provide comprehensive, evidence-based healthcare to this patient population.